Promoting the Study of Inorganic Nomenclature in University Students through an Educational Strategy Using M-learning - Danny Arteaga; Andrea Carolina Cabanzo; Paola Gómez Buitrago (Science Education International, 2025)
Herein, we explore the impact of using a flipped classroom approach on the achievement of learning outcomes in the International Union of Pure and Applied Chemistry (IUPAC) inorganic nomenclature in fundamental chemistry courses at the university level. In addition, the study sought to evaluate student attitude, motivation, and engagement when using this dynamic and interactive learning strategy. We assessed learning competencies through workshops and post-activity tests. To determine the effectiveness of this educational strategy, we compared the results between the experimental and control groups using the average scores from each assigned task. Atotal of 72 students participated in the activity, and non-probabilistic sampling was used to select the study population. In the activities, the students in the experimental group achieved higher average grades compared to those in the control group. 97.6% of students in the experimental group passed the final test, with grades ranging from 3.0 to 5.0 (where 5.0 equals 100%), whereas only 58.6% of the control group passed the final test. The statistical analysis of the classroom implementation results showed that using the inverted approach helped students learn key concepts and IUPAC nomenclature rules, enhancing their ability to identify and name different inorganic compounds. These findings also indicated that student-centered educational activities enhance competence, boost motivation, and improve subject understanding.